THE PROS AND CONS OF THE RELATIONSHIP BETWEEN PERSONALITY AND LEADERSHIP OR MANAGERIAL BEHAVIOR OF NURSING MANAGER - Joko Gunawan (Belitung Raya Foundation, 2016)
Dear Editor, "Complex role in complex times" that is what nurse managers have as the one on the most key roles in the hospital.1 They are not just about managing staff schedules, but also need to have a vision and able to inspire them.2 Thus, competent nurse managers are needed. Research suggests that employees and employers are looking for similar characteristics or personality traits in their leaders. Personality trait refers to the dimensions of individual differences in tendencies to show consistent patterns of thoughts, feelings and actions.3 Personality trait seems able to explain why a person acts the way he/she does when in a leadership position. Research aggregated the results of 222 correlations contained in 73 studies of personality and leadership performance by involving 25,000 managers from every level in organizations across every industry sector.4 There were four of the five dimensions of the big five personality were significantly correlated with leadership emergence and effectiveness with adjustment / emotional stability as the best predictor, and agreeableness as the weakest predictor.4 Scholars who believe in data, these findings definitively indicate that personality predicts leadership behaviors across all organizational levels and industry sectors, and does so more powerfully than any known alternative.5 Personality traits relate to leader behaviors to a greater extent and less ambiguously than earlier reviews had suggested.6 However, although there are clear evidences in examining the relationship between personality and leadership or managerial behavior, it is also important that there are cons about the degree to which personality is related to managerial or leadership behavior Literature indicates that personality traits cannot be concluded to determine leadership with some considerations: (1) it is impossible to find one specific personality trait that characterizes leaders and (2) it is impossible to isolate a number of traits, which combined, explain leadership.7 Thus, it is failed to investigate a clear relationship between personality and leadership. It might be other indications that traits work with other factors in the leadership or managerial behavior.8 Study investigated the relationship between personality and transformational leadership, and now some agreement that there may be five super-traits (extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience) are related to managerial or leadership behavior. But, it is important to note the effect sizes were not large 5 Another study emphasized that "one should be careful in generalizing our findings on the relation of traits to leadership perceptions to other areas of leadership.9" The findings could not be directly concluded that there are traits that would generally predict the performance of a leader's work group or organization, nor do they imply that there are certain types of leadership behaviors that will generally produce superior performance.9 On the other hand, the main issue in management research is what kind of behavior managers exhibit and how behavior influences the outcome of the organization. Why leaders behave the way they do adheres to a general issue in psychology, the relationship between personality and behavior. It is not a burning issue in leadership 5. Additionally, there is no evidence to support that managers are primarily recruited based on their personality traits. Managers are not recruited or promoted based on their personality in formal organizations. Managers are hired primarily due to their formal competence and previous merits.10 Finally, the correlation between personality trait and managerial or leadership behavior remains inconclusive. However, it is agreed that personality cannot be excluded from leadership and management.